Effect of Cutting Management on Seed Yield and its Quality in Grasses - R.K. BHATT; R.K. TRIPATHI; H.S. TIWARI (Seed Research, 2026)
In Chrysopogon fulvus, Setaria sphacelata, Panicum maximum and Penisetum pedicellatum maximum seed yield was recorded from the crops cut at 30 cm height from the ground at vegetative stage. Whereas in Cenchrus ciliaris higher seed yield was recorded from the uncut crop during the second year of crop establishment. The seed yield and seed quality were affected to a great extent and cutting height of 15 cm induced vegetative growth. Cutting of crops at 30 cm height was beneficial for the production of additional biomass and maximization of synchronized harvested seeds yield. The quality of seeds as indicated by seed test weight and germination was also maintained even if the crop was cut at 30 cm plant height.